2003
DOI: 10.1007/bf03021032
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal + PCA morphine improves analgesia during the first 24 hr after major abdominal surgery compared to PCA alone

Abstract: P Pu ur rp po os se e: : To compare, over a 48-hr follow-up period, the analgesia and side-effects of patient controlled iv analgesia (PCA) with morphine alone vs combined intrathecal and PCA morphine (IT+PCA) in patients undergoing major abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
5
37
0
2
Order By: Relevance
“…In this study, 3 (9.4%) out of 32 patients in the ITM group presented with bradypnoea and 1 (3.1%) presented with excessive sedation in the first 12 postoperative hours, which was higher than previous reports (range 0%-3%). (6,23) Among them, one patient with excessive sedation required temporary postoperative ventilator support because of hypercarbia. In contrast to our findings, Devys et al reported no bradypnoea following ITM and IV PCA morphine (no background infusion) after abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 3 (9.4%) out of 32 patients in the ITM group presented with bradypnoea and 1 (3.1%) presented with excessive sedation in the first 12 postoperative hours, which was higher than previous reports (range 0%-3%). (6,23) Among them, one patient with excessive sedation required temporary postoperative ventilator support because of hypercarbia. In contrast to our findings, Devys et al reported no bradypnoea following ITM and IV PCA morphine (no background infusion) after abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…(5) The combination of intrathecal morphine (ITM) and IV patient-controlled analgesia (PCA) has been demonstrated to be a viable alternative method of analgesia. (6,7) Nevertheless, patients with systemic opioids and ITM have an elevated risk of early or delayed respiratory depression and should be monitored closely. (8) Blocking of the parietal nociceptive afferent nerves via surgical-site infusion (SSI) of local anaesthetics is currently widely recognised as a useful adjunct to standard analgesic regimens after major surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the two opioids may provide an optimal analgesic regimen to cover analgesic requirements for the first 24 hr. 1 Previous studies that have demonstrated the benefit of intravenous opioids in abdominal surgery have either compared ITS to intravenous morphine PCA, 16 ITM to intravenous morphine PCA, 7 or a combination of ITS and ITM to intravenous morphine PCA. 18 We decided to conduct this prospective study using doses of ITM and ITS based on experience gained in different surgical settings.…”
Section: Discussionmentioning
confidence: 99%
“…5,28,29 However, in contrast to orthopedic or obstetrical procedures, the optimal dose of ITM for major abdominal surgery has not yet been determined, although others have successfully used ITM doses in the range that we have studied. 6,7 It is possible that had we used a lower dose of ITM, then the analgesic benefit of ITS may have been unveiled. Although this combination may appear attractive at institutions unable to closely monitor patients overnight, this hypothesis needs to be formally tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation